The Impact of Media Card Match Circle and the Challenge-Based Learning (CBL) Learning Model on the Learning Outcomes of Pancasila Education in Elementary School Students - Rahma, Sitti; Suardi, Suardi; Muhajir, Muhajir (Universitas Cokroaminoto Palopo, 2024)
The low learning outcomes of students are the main problem studied in this article This study employs a quasi-experimental design with a Nonequivalent Control Group model to assess the impact of implementing the Challenge Based Learning (CBL) model supported by Card Match Circle media on Pancasila Education learning outcomes. The study population consists of fifth-grade students at SD Inpres Karuwisi 2 Makassar, divided into two groups: the experimental group (class VA) and the control group (class VC), each comprising 24 students. Data collection was carried out through tests, questionnaires, and observation sheets at the beginning and end of the research period. The analysis results indicate that the implementation of the CBL model with Card Match Circle media significantly improved students' learning outcomes compared to conventional teaching methods, with the experimental group's average posttest score (80.37) being higher than the control group's (72.41). Statistical analysis confirms that this model is effective in enhancing material comprehension, as well as students' collaboration and communication skills. These findings align with previous studies showing that the CBL approach with interactive media can create a more engaging and relevant learning experience, motivating students to be more actively involved in their education.